On Self‐Similar and Multifractal Models for the Scaling of Extreme Bursty Fluctuations in Space Plasmas - Watkins, N. W; Hnat, B; Chapman, S. C (Extreme Events and Natural Hazards: The Complexity Perspective, 2012)
This chapter contains sections titled: Introduction Motivation for a Self‐Similar, Stable, Description Data Sets Used General Consequences of any Self‐Similar Model Specific Consequences of a Particular Choice of Self‐Similar Model Limitations of the LFSM Model Conclusions